Consecuencias personológicas del abuso sexual. - Rivera Arias, Angela Ileana (2015)
The present investigation of case analysis, aims to identify the cognitive schemes constructed from sexual abuse, the same that was developed under the theoretical underpinnings of the current cognitive-behavioral, which allows to explain cognitive processes that are built on the psyche of a victim of sexual abuse, from the negative perception that this gives the traumatic event, resulting in the alteration of the personality.